Evaluación del efecto de un inhibidor de etileno en el comportamiento poscosecha de tomate cherry (solanum lycopersicum L), en tres índices de color en el Campus Salache. - Chiliquinga Guato, Alexandra Elizabeth (2023)
This research project was developed at the Cotopaxi Technical University, Salache campus, in the laboratory from Agricultural Engineering degree. The research aim was to assess an ethylene inhibitor effect on the postharvest behavior from cherry tomato (Solanum lycopersicum L), into three color indices. Which it was used a randomized complete block design (DBCA) with a 3x3 factorial arrangement, by giving a 9 treatments and 27 experimental units total. The applied ethylene inhibitor doses were 0, 0.5 and 1 cm2, what was the used size each tarine into postharvest. The assessed indicators were pH, total solids, firmness, pests and diseases weight and incidence. The following results were got: The best harvest index was "C1" (color index 4) presenting a 2% weight loss for the variable firmness, it presents a 0.98% at pH 4.15 and for soluble solids 7.17° Brix. In the best dose was the "IE3" (1cm2), giving positive results into weight with 1.15%, for firmness was got 1.86% and in the physiopathies variable 85.36%.